Wood Photo Transfer to Improve Santriwati Entrepreneurship at Al Fatah Shuffah Hizbullah Islamic Boarding School, Samarinda City: Transfer Foto ke Kayu Untuk Meningkatkan Kewirausahaan Santriwati di Pondok Pesantren Al Fatah Shuffah Hizbullah, Kota Samarinda - Karyati, Karyati; Widiati, Kusno Yuli; Karmini, Karmini; Sari, Diah Rakhmah; Sarminah, Sri; Syafrudin, Muhammad; Mulyadi, Rachmad; Karhani, Muna (Universitas Lancang Kuning, 2025)
The curriculum for santriwati in Islamic boarding schools encompasses not only religious studies but also the development of entrepreneurial skills. One such skill with potential economic value is wood photo transfer (WPT), which utilises wood as the basic material. The selection of this extension theme was based on the availability of wood raw materials in various sources around the boarding school. The objective of the counselling was to provide female students at the pesantren with information and skills on WPT making techniques. The counselling involved a theoretical explanation of the material and a practical demonstration of wood-based WPT. A total of 14 female students at one of the Islamic boarding schools in Samarinda received hands-on training in making WPT. Of the trainees, 50% were able to complete the practice of making WPT. The skills required to produce WPT can be developed in order to pursue hobbies or as a potential business opportunity with the aim of increasing the income of santriwati.